Fusobacterium Species and Subspecies Differentially Affect the Composition and Architecture of Supra- and Subgingival Biofilms Models - Thurnheer, Thomas; Karygianni, Lamprini; Flury, Manuela; Belibasakis, Georgios N. (Frontiers in Microbiology, 2019)
Fusobacteria are common obligately anaerobic Gram-negative bacteria of the oral cavity that may act as a bridge between early and late colonizing bacteria in dental plaque, and have a role in oral and extra-oral infections. Fusobacterium nucleatum has a crucial role in oral biofilm structure and ecology, as revealed in experimental and clinical biofilm models. The aim of this study was to investigate the impact of various Fusobacterium species on in vitro biofilm formation and structure in three different oral biofilm models namely a supragingival, a supragingival “feeding”, and a subgingival biofilm model. The standard six-species supragingival and “feeding” biofilm models employed contained Actinomyces oris, Candida albicans, Streptococcus mutans, Streptococcus oralis, Veillonella dispar, and Fusobacterium sp. The subgingival biofilm model contained ten species (Actinomyces oris, Campylobacter rectus, Fusobacterium nucleatum ssp. nucleatum, Porphyromonas gingivalis, Prevotella intermedia, Streptococcus anginosus, Streptococcus oralis, Tannerella forsythia, Treponema denticola, and Veillonella dispar). Six different Fusobacterium species or subspecies, respectively, were tested namely F. nucleatum ssp. fusiforme, F. nucleatum ssp. nucleatum, F. nucleatum ssp. polymorphum, F. nucleatum ssp. vincentii, F. naviforme, and F. periodonticum). Biofilms were grown anaerobically on hydroxyapatite discs in 24-well culture dishes. After 64 h biofilms were either harvested and quantified by culture analysis or proceeded to fluorescent in situ hybridization (FISH) and confocal laser scanning microscopy (CLSM). All Fusobacterium species tested established well in the biofilms, with CFUs ranging from 1.4E+04 (F. nucleatum ssp. fusiforme) to 5.6E+06 (F. nucleatum ssp. nucleatum). The presence of specific Fusobacterium sp/ssp induced a significant decrease in C. albicans levels in the supragingival model, and in V. dispar levels in the ‘feeding’ supragingival model. In the subgingival model, the counts of A. oris, S. oralis, P. intermedia, P. gingivalis and C. rectus significantly decreased in the presence of specific Fusobacterium sp/ssp. Collectively, this study showed variations in the growing capacities of different fusobacteria within biofilms, affecting the growth of surrounding species and potentially the biofilm architecture. Hence, clinical or experimental studies need to differentiate between Fusobacterium sp/ssp, as their biological properties may well vary.